Serum Survivin Increases in Prolactinoma - Dellal, Fatma Dilek (J Clin Med Res, 2015)
BACKGROUND: Prolactinoma is the most common adult pituitary adenoma. Survivin is a member of the family of inhibitors of apoptosis proteins. Its expression is observed in many tumors. Survivin expression has shown in prolactinoma tissue before but no study exists showing serum survivin level. The aim of the present study was to investigate serum survivin levels in patients with prolactinoma and demonstrate its value in diagnosis of the disease. METHODS: The group of patients consisted of 25 women, aged from 17 to 51 years. As a control group, 21 healthy women, aged from 22 to 45 years were included. Twenty patients had microprolactinoma, while five patients had macroprolactinoma. All patients had received dopamine agonist treatment. Serum survivin levels were measured in all of the groups. RESULTS: Survivin levels were significantly higher in prolactinoma patients compared to controls (19.04 (10 - 38) pg/mL; 15.05 (8 - 22) pg/mL; P = 0.042). There was no difference between microadenoma and macroadenoma patients in survivin levels (19.22 (10 - 38) pg/mL; 18.40 (16 - 22) pg/mL; P = 0.914). In correlation analysis, survivin was not correlated with other parameters. CONCLUSIONS: We consider that higher survivin levels might be a molecular marker predicting the presence of prolactinoma and may be useful for the diagnosis. But large-scale research is needed to clarify its role in diagnosis of prolactinoma patients.